Effect of Ethephon on ripening and postharvest quality of mango (Bangladesh Journal of Agricultural Research, 2019)
The experiment was conducted at the laboratory of Postharvest Technology Division, BARI to evaluate the effect of postharvest application of 6 concentrations (0, 250, 500, 750, 1000 & 10000 ppm) of ethephon on ripening and postharvest qualityof mango (cv. Langra) fruits harvested at mature green stage on 3rdweek of June in 2011 and 2012. The treated fruits were assessed for physiological changes such as ripening %, weight loss (%), biochemical aspects such as TSS (0Brix), titratable acidity (%), reducing sugar (%), total sugar (%), ascorbic acid content (mg/100g), total carotenoids (μg/100g), carbon di oxide production (ml/g fruit) and residual level of the applied ethephon during storage period. The observations were recorded at 2 days interval during 6 days storage at ambient condition (23±2°C with 80±5% RH). Complete yellow color (full ripe) was developed on the fruits treated with 500-1000 ppm ethephon at 4 days of storage while yellowish green and greenish yellow color was developed on 250 ppm treated and control fruits, respectively, and 10000 ppm ethephon treated fruits overripened at this period. At 6 days of storage, 250 ppm ethephon treated fruits got ripen and 500-1000 ppm ethephon treated fruits overripened whereas 10000 ppm treated fruits got rotten and control one was still unripe. Irrespective of ethephon treatments, weight loss of fruits, TSS, reducing sugar, total sugar, carbon di oxide production and total carotenoid showed increasing trends upto 6 days whereas titratable acidity, ascorbic acid and residue level of ethephon showed decreasing trends in both years. At 4 days of storage, 750-1000 ppm ethephon dipped fruits induced uniform attractive yellow color while untreated control fruits remained yellowish greenish (unripe) even after 6 days of storage. At 6 days of storage TSS, reducing sugar, toatal sugar, ascorbic acid and total carotenoid content were found maximum in 750-1000 ppm treated fruits compared to 250-500 ppm treated fruits. The residue level of ethephon in mango fruits treated with ethephon concentrations (250-1000 ppm) at 6 days of storage was found below 2 ppm (0.1 1ppm-0.54 ppm), which is safe for human consumption. Therefore, mangoes ripened by using ethephon @ 750-1000 ppm can be consumed safely without any health risk.Bangladesh J. Agril. Res. 44(3): 453-467, September 2019